Finite simple groups with Hall {2, r}-subgroups, r π(G) {2, t}, t π(G) - Bashun, S. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.542 We describe finite simple groups with Hall biprimary subgroups of even order that contain Sylow subgroups of odd order of the G-group, except one of Sylow’s subgroups of odd order.